2020
DOI: 10.1002/adhm.202000255
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial Progenitor Cell‐Derived Extracellular Vesicles: A Novel Candidate for Regenerative Medicine and Disease Treatment

Abstract: Extracellular vesicles (EVs) are a heterogeneous group of membranous structures, which can be secreted by most cell types. As a product of paracrine secretion, EVs are considered to be a regulatory mediator for intercellular communication. There are many bioactive cargos in EVs, such as proteins, lipids, and nucleic acids. As the precursor cell of vascular endothelial cells (ECs), endothelial progenitor cells (EPCs) are first discovered in peripheral blood. With the development of studies about the functions o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(35 citation statements)
references
References 153 publications
0
32
0
Order By: Relevance
“…This observed effect may be exerted through exosomes or a variety of paracrine mechanisms [ 59 , 60 ]. It was proved that EPCs create local nutritional support environments by producing microvesicles, exosomes, and growth factors which promote cell proliferation and cell biological motility maintenance [ 61 63 ]. It was reported that EPCs derived exosomes transplantation significantly accelerate bone regeneration in rats [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…This observed effect may be exerted through exosomes or a variety of paracrine mechanisms [ 59 , 60 ]. It was proved that EPCs create local nutritional support environments by producing microvesicles, exosomes, and growth factors which promote cell proliferation and cell biological motility maintenance [ 61 63 ]. It was reported that EPCs derived exosomes transplantation significantly accelerate bone regeneration in rats [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…These challenges need to be addressed before exosomes can proceed to clinical application. [49] miR-10b-5p Ameliorate cardiac fibroblast activation Preclinical evidences (in vitro) [89] miR-146a-5p and miR-146b-5p Inhibit the migration and angiogenesis Preclinical evidences (in vitro) [88] Macrophages and leukocyte NA Promote vascular smooth muscle cells migration and adhesion, which may be mediated by the integration of extracellular vesicles into vascular smooth muscle cells and the subsequent downstream activation of ERK and Akt Preclinical evidences (in vitro) [51] Biomarkers of atherosclerosis Clinical evidences [50] Cardiac stromal cells miR-21-5p…”
Section: Resultsmentioning
confidence: 99%
“…The cardiac precursor cell-secreted exosomes rich in PAPP-A had a cardioprotection profile through releasing IGF-1 via proteolytic cleavage of IGFBP-4, resulting in IGF-1R activation and intracellular Akt and ERK1/2 phosphorylation [87]. It was found that exosomes secreted by endothelial progenitor cells derived from patients with coronary atherosclerotic heart disease could inhibit the migration and angiogenesis through expressing more miR-146a-5p and miR-146b-5p [88]. Another study indicated that normoxia endothelial progenitor cell-derived exosomes rich in miR-10b-5p could significantly ameliorate cardiac fibroblast activation in vitro [89].…”
Section: Future Perspectivesmentioning
confidence: 99%
“…[59,60]. It was proved that EPCs create local nutritional support environments by producing microvesicles, exosomes and growth factors which promote cell proliferation and cell biological motility maintenance [61][62][63]. It was reported that EPCs derived exosomes transplantation signi cantly accelerate bone regeneration in rats [37].…”
Section: The Effects Of P38 Sirna On the Osteogenic Differentiation Omentioning
confidence: 99%